The Relation of Vitamin D Levels to Isokinetic Muscular Strength In Adolescent Athletes - Sabriye Ercan (Acta Medica Alanya, 2019)
Aim: To determine the relation between vitamin D levels and isokinetic muscular strength in athletes, and to compare the muscular strength between athletes with and without vitamin D deficiency. Methods: The records in the sports medicine clinic were examined, where the general medical examinations and performance analyses of the athletes had been conducted. The data of the athletes were examined, whose serum 25-OH vitamin D levels had been determined and isokinetic knee flexion-extension muscular strength test had been conducted. Age, height, body weight, discipline of sports, the year of beginning to sports and training duration per week (hours/week) were recorded for each athlete. The athletes were separated into two groups as vitamin D levels below 20 ng/mL (Group 1) and above 20 ng/mL (Group 2). Results: There was not any statistically significant difference between the demographic data and training data of the groups (p˃0.05). Vitamin D deficiency was found in 44% of all the athletes. The average vitamin D level was 13.8 ng/mL for Group 1, and 27.2 ng/mL for Group 2 (p:0.001). The serum calcium and serum phosphor levels were similar (p˃0.05). The isokinetic muscular strength test did not yield a difference between the two groups. It was found that vitamin D levels did not show any correlation with demographic data, training details and with any parameter of muscular strength (p˃0.05). Conclusion: In this study, there are no difference in effect of vitamin D on muscle strength, but significant results could be obtained in other studies with large participants.